Impact of Character Education on Social Behavior of Religious School Students (Study on Students of MTs Al-Khairiyah Panecekan, Kubang Puji Village, Pontang District, Serang-Banten) - Najmudin Najmudin; Ma'zumi Ma'zumi; Sujai Sujai; Roimun Roimun; Iis Farida; Abdul Aziz (L, 2022)
This study aims to determine the impact of character education on the social behavior of the students of Madrasah Tsanawiyah (MTs) Al-Khairiyah Panecekan, Kubang Puji Village, Pontang District, Serang Regency, Banten. The population in this study were students of Madrasah Tsanawiyah (MTs) Al-Khairiyah Panecekan, Kubang Puji Village, Pontang District, Serang-Banten Regency, totaling 98 students. The respondents of this study were 98 students. The research method used is a quantitative method with data collection methods in the form of a questionnaire. The data were analyzed using instrument tests in the form of validity and reliability tests, classical assumption tests in the form of normality tests and heteroscedasticity tests, and hypothesis tests in the form of simple linear regression tests and correlation coefficient tests. The results of this study indicate that character education has a significant positive impact on the social behavior of students at MTs Al-Khairiyah Panecekan, Kubang Puji Village, Pontang District, Serang Regency, Banten. the influence of character education variables on social behavior is 19.7% while the rest is influenced by other variables not examined in this study.